Sharia Finance Literacy and Determinants on Creative Economy - Ma’ruf, Ahmad (International Journal of Economics, Business and Management Studies, 2019)
This study was aimed to discover the literacy rate of sharia finance and the determinants on Creative Economy actors, case study in Yogyakarta Special Region. This was a quantitative study with descriptive statistics as the analysis method. The sample of data was taken in November 2018-January 2019 toward creative economy actors in small and medium enterprises level (SME). The independent variables that were used include gender, age, education level, and length of business, while the dependent variable was literacy rate of sharia finance. The results of this study have indicated that the creative economy actors in Yogyakarta Special Region were categorized as sufficient literate, and there are many of them who included in less literate category. The variables of gender, age, education level, and the length of business have significant impact toward the literacy rate of sharia finance on creative economy at the scale of SME in Yogyakarta Special Region.